FEVER: Global histories of (a) disease, 1750-1840 - Gänger, Stefanie; Huang, Yijie; Sure, Jenny; Göltl, Teresa (Universität, 2025)
Fever is one of the most basic and pervasive of human experiences. While fever is in some measure a universal feature of humans’ material existence, however, its relevance and meaning, its sensory experience and implications, differed from one historical context to another. This ERC project studies fever globally, particularly in societies within or tied to the Atlantic world, in the century spanning from the 1750s to the 1840s - a time when fever was not only considered the most common ailment that afflicted mankind, but also its most fatal one; ‘more persons died of fever than of all other ailments combined’, as contemporaries saw it. Given that fever was a threatening, ubiquitous presence for men and women around 1800, we know surprisingly little about it; as one medical historian recently put it, ‘fever has been the invisible elephant in the china shop of the medical past’. Premised upon archival research in countries across the world, the FEVER project studies various aspects of the history of fever around 1800, such as: the unusual prevalence of fevers in the period’s medical record; the period’s means of diagnosis, especially pulse diagnosis, in a period prior to the advent of thermometry; the role of emotions as both causes and symptoms of fever; ‘obstinate’, chronic, relapsing or seasonal fevers and their long-term consequences; vernacular and non-European fever remedies; and fever’s resonance and relation with similar or affine disease concepts in other, non-European empires. The project poses questions fundamental to our understanding of both the past and the present: about the rise and fall of diseases, the credibility of medical knowledge, and how cultural and historical contexts affect suffering and physiology, and vice versa.